The Challenges of Canadian Pharmacare Are More Complicated Than Acknowledged; Comment on "Universal Pharmacare in Canada" - Kristina M. L. Acri née Lybecker (Kerman University of Medical Sciences, 2021)
This commentary considers two editorial pieces, written by Hajizadeh and Edmonds, and Lewis, which address universal pharmacare in Canada. The pieces focus on the social inequities of the existing system and the challenges of successful implementation. After identifying the significant strengths of both articles, this commentary then delves into the reasons why universal pharmacare may not be the solution, and identifies numerous thorny issues that will complicate the implementation of such a publicly funded program. Both discussions point to the need for caution and transparency going forward.